Embodied computation and spatiomateriality – Exploring complexity through cybermodelling - Aileen Iverson-Radtke; Otto Paans (Agathón)
To improve its effectiveness, today’s digital design requires ‘bounded complexity’ due to the nature of the parameters involved in modelling, creating a balance between the complexity of the design problem and the tool. In addition to parameters related to form and context, a third element emerges, ‘spatiomateriality’, reflecting the connection between objects and space in physical making, as materials respond directly to changes induced by the context. This study explores a new way of using spatiomateriality through an innovative digital-analogue interface called ‘cybermodelling’: by linking real-time environmental data to digital models, cybermodelling creates ‘live’ models that react to changing conditions, generating digitised spatiomateriality. Such computational design environments support phenomenological aspects of form and space by integrating real and virtual spheres.